PERSEPSI GURU TERHADAP PELAKSANAAN FUNGSI MANAJERIAL KEPALA SEKOLAH DALAM BIDANG KURIKULUM DI SD NEGERI KECAMATAN BARANGIN KOTA SAWAHLUNTO - Sumartini , (Jurnal Bahana Manajemen Pendidikan, 2013)
The background research is phenomenon indicating implementation of headmaster managerial functions in curriculum lacking well-managed. This research aim to obtain information on teachers’ perceptions on the implementation of principal managerial functions head master in curriculum of SD Negeri Kecamatan Barangin Kota Sawahlunto. The population was 170 teacher of SD Negeri Kecamatan Barangin Kota Sawahlunto. Samples taken are 25% of the total population is 43 people, instrument used in this research was the questioners which has been tasted for its validity and reability. In general, the perception of teacher on the implementation of managerial functions head master in curriculum of SD Negeri Kecamatan Barangin Kota Sawahlunto in the category of good length with an average score overall was 84,36%. Keywords : Managerial Functions.